Crystal structure of γ-methyl l-glutamate N-carboxy anhydride - Kanazawa, Hitoshi (Acta Crystallogr E Crystallogr Commun, 2015)
In the title compound, C(7)H(9)NO(5), alternative name N-carboxy-l-glutamic anhydride γ-methyl ester, the oxazolidine ring is essentially planar with a maximum deviation of 0.020 (3) Å. In the crystal, molecules are linked by N—H⋯O hydrogen bonds between the imino group and the carbonyl O atom in the methyl ester group, forming a tape structure along the a-axis direction. The tapes are linked by C—H⋯O interactions into a sheet parallel to the ac plane. The tapes are also stacked along the b axis with short contacts between the oxazolidine rings [C⋯O contact distances = 2.808 (4)–3.060 (4) Å], so that the oxazolidine rings are arranged in a layer parallel to the ab plane. This arrangement of the oxazolidine rings is very preferable for the polymerization of the title compound in the solid state.